Rate and Predisposing Factors for Sacroiliac Joint Radiographic Progression After a Two‐Year Follow‐up Period in Recent‐Onset Spondyloarthritis - Maxime Dougados; Christophe Dematteï; Rosaline van den Berg; V. Vo Hoang; F. Thévenin; M. Reijnierse; Damien Lœuille; A. Feydy; Pascal Claudepierre; Désirée van der Heijde (2016)
Objective To evaluate the rate of radiographic structural progression in the sacroiliac (SI) joints in patients with radiographic or nonradiographic axial spondyloarthritis (SpA), and to determine factors predisposing to such progression, over 2 years. Methods Patients with recent‐onset axial SpA (from the Devenir des Spondyloarthropathies Indifferérenciées Récentes cohort) were assigned a radiographic SI joint score according to the modified New York criteria. Demographic characteristics, smoking status, HLA–B27 positivity, inflammation on magnetic resonance imaging (MRI) of the SI joints, disease activity, and treatment were investigated as potential predisposing factors. The main analysis consisted of the evaluation of the switch from nonradiographic to radiographic axial SpA, but other definitions of radiographic progression were also evaluated. Results Of the 708 patients enrolled, 449 had baseline and 2‐year pelvic radiographs. Of these patients, 47% were men. Their mean ± SD age was 34 ± 9 years, 61% were B27 positive, and 37% had inflammation of the SI joints on MRI. The percentages of patients who switched from nonradiographic to radiographic axial SpA (4.9% [16 of 326]) and from radiographic to nonradiographic axial SpA (5.7% [7 of 123]) were low. The mean ± SD change in the total SI joint score (range 0–8) was small (0.1 ± 0.8) but highly significant ( P < 0.001). The potential baseline predisposing factors for meeting the modified New York criteria in the multivariate analysis were current smoking, HLA–B27 positivity, and inflammation of the SI joints on MRI, with odds ratios of 3.3 (95% confidence interval [95% CI] 1.0–11.5], 12.6 (95% CI 2.3–274), and 48.8 (95% CI 9.3–904), respectively. Conclusion Our findings suggest that structural progression does exist in early SpA, but it is quite small and observed in a small number of patients, and that environmental (smoking status), genetic (HLA–B27 positivity), and inflammation (inflammation of the SI joints on MRI) markers might be independent predisposing factors for progression.